IMPACT OF TROPICAL CYCLONE SEROJA ON RAINFALL AND WIND SPEED IN EAST NUSA TENGGARA PROVINCE - Kaha, Astried Valentine; Baskoro, Winardi Tjahyo; Sumaja, Kadek; Sukarasa, I Ketut; Paramarta, Ida Bagus Alit; Sandi, I Nengah (Indonesian Physical Review, 2024)
Tropical cyclone phenomenon can give impacts such as heavy rain, strong winds, and high waves around its growth area. One of the tropical cyclones that has occurred is Seroja Tropical Cyclone which formed in the Sawu Sea on April 3, 2021. Therefore, this study aims to determine the effect of Seroja Tropical Cyclone on rainfall and surface wind speed in East Nusa Tenggara Province and the percentage comparison of rainfall and wind speed during the Seroja tropical cyclone event with the normal value of rainfall and surface wind speed over a 10-year period. The data used are daily rainfall and surface wind speed data during the Seroja tropical cyclone event, namely April 3 to 12, 2021 and daily average rainfall and wind speed data in April for 10 years in several affected districts in East Nusa Tenggara Province. Data processing is done by calculating the percentage comparison of rainfall and wind speed during the Seroja Tropical Cyclone event with normal rainfall and wind speed in several regions in East Nusa Tenggara. Based on the analysis, heavy to extreme rainfall and strong winds were found in several districts at a radius of about 400 km from the center of the cyclone. Although the category of this tropical cyclone is low, it is able to give impacts in the form of heavy to extreme rainfall and strong winds in the surrounding area. So it can be concluded that the tropical cyclone category does not directly affect rainfall and wind speed in an area, but the distance between the area and the center of the tropical cyclone is more influential in increasing rainfall and wind speed in an area. This is also proven by Sumaja's research in the case of tropical cyclones LUA and Narelle.